2017
DOI: 10.1136/bmjopen-2017-015941
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of mortality rates and causes of death in children under 5 years old in Beijing, China from 1992 to 2015 and forecast of mortality into the future: an entire population-based epidemiological study

Abstract: ObjectivesTo analyse trends in mortality and causes of death among children aged under 5 years in Beijing, China between 1992 and 2015 and to forecast under-5 mortality rates (U5MRs) for the period 2016–2020.MethodsAn entire population-based epidemiological study was conducted. Data collection was based on the Child Death Reporting Card of the Beijing Under-5 Mortality Rate Surveillance Network. Trends in mortality and leading causes of death were analysed using the χ2 test and SPSS 19.0 software. An autoregre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 16 publications
4
30
2
Order By: Relevance
“…Our finding established that neonatal death accounted for nearly half of the under-five deaths, which was in agreement with a 22 years trend analysis done in China, reports from WHO, and global systematic analysis [3,30,31]. In addition, similar to Demographic Health Survey (DHS) studies from Uganda and Ethiopia, our report also showed that more than two-third of the under-five deaths occurred during their infantile period [4,5,32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding established that neonatal death accounted for nearly half of the under-five deaths, which was in agreement with a 22 years trend analysis done in China, reports from WHO, and global systematic analysis [3,30,31]. In addition, similar to Demographic Health Survey (DHS) studies from Uganda and Ethiopia, our report also showed that more than two-third of the under-five deaths occurred during their infantile period [4,5,32].…”
Section: Discussionsupporting
confidence: 92%
“…In a couple of population-based epidemiological studies done in China, premature birth and birth asphyxia were among the top five leading causes of under-five mortality [28,31]. Our study also identified premature birth and birth asphyxia to be the top causes of under-five mortality.…”
Section: Discussionsupporting
confidence: 58%
“…Prevention interventions targeting specific age groups are required since the distribution of causes of death varied across age groups [16]. We found that the maternal and perinatal diseases accounted for the largest proportion of infant deaths, followed by congenital diseases.…”
Section: Resultsmentioning
confidence: 85%
“…More attention should be paid to the primary and secondary prevention measures, including antenatal corticosteroids and kangaroo mother care, for preterm birth complications, a major part of maternal and perinatal diseases [17]. In addition, pregnancy at an appropriate age and the prenatal diagnosis are suggested to reduce the occurrence of congenital heart disease [16,18,19]. Our study indicated that the main causes of death for children aged 1-4 years were non-communicable diseases, while a national analysis reported injuries were the leading causes at this age group in China [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation